Akibat Hukum Notaris Mengubah Akta Pengikatan Perjanjian Jual Beli (PPJB): Studi Putusan Nomor: 688/PDT.BTH/2022/PN.JKT.SEL - Selly Marlianti; Mella Ismelina Farma Rahayu (UNES Law Review, 2023)
The issue of the binding of the sale and purchase agreement (PPJB) in this case originates from the turmoil of buying and selling shop houses in Pasar Minggu, South Jakarta, between Harijanto Latifah and Tri Rahadian Sapta Pamarta, culminating in a civil lawsuit by Tri Rahadian at the South Jakarta District Court. The South Jakarta District Court decided that Tri Rahadian is the rightful owner of the land and shop house in Pasar Minggu, South Jakarta, and annulled the Deed of Agreement to Buy and Sell (PPJB) deemed defective and legally ineffective. The issue that will be the basis for analysis is the legal consequences for the aggrieved sellers due to the unlawful actions of the notary. The research results show legal protection for the sellers regarding changes to the Deed of Agreement to Buy and Sell (PPJB) by the Notary without their knowledge. Thus, the sellers have the right to annul changes made by the Notary without their approval, and ethical violations by the Notary can result in legal claims and sanctions in accordance with applicable regulations. Legal consequences that the Notary may face include the invalidation of the deed, ethical sanctions, and potential civil lawsuits. Sellers have the right to question the validity of changes made by the Notary and can file compensation claims. Administrative sanctions that may be imposed on the Notary emphasize the importance of compliance with professional ethical codes.